The dosymetric parameters investigation of the pulsed gamma radiation source based on betatron - Miloichikova I. A. Irina Alekseevna; Stuchebrov S. G. Sergey Gennadevich; Wagner A. R. Aleksandr Rudolfovich; Zhaksybaeva G. K. Gulnur Kapizkyzy (2014, 2014)
Title screen